Composite materials obtained from textile fiber residue - Mulinari, D. R. [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP]; Cioffi, M. O. H. [UNESP]; Lima, C. A. A.; Baptista, C. A. P. R.; Rocha, G. J. M. (Sage Publications Ltd, 2011)
This article presents the use of fibers residue from textile industry to minimize environmental problems associated with material accumulation. Composite materials utilizing textile fiber residues and high density polyethylene were prepared. Effect of treatment with hot water on fibers to prepare composites was studied to provide an improvement in mechanical properties of these materials. This treatment on fibers was evaluated by X-ray diffraction and scanning electron microscopy techniques. Experimental results of mechanical properties indicated higher mechanical strength for treated fiber composites compared to the untreated fiber composites.
Keywords: reuse; textile fibers; polymer-matrix composites; mechanical properties